Feasibility Study Of Website-Based Educational Media “Sahabat Disminore” - Lestari, Meti Widiya; Silalahi, Uly Artha; Putri, Fadila (Buletin Penelitian Kesehatan, 2024)
Introduction: Dysmenorrhea is a reproductive health problem that is often experienced by adolescent girls and requires special attention from midwives. To overcome this, effective health promotion is needed. In this digital era, the use of mobile devices is increasing, including easy-to-access website access, so that searches can be done anytime and anywhere for information. Midwives can take advantage of this opportunity to conduct health promotion, one of which is by using the website as a means to provide information related to dysmenorrhea.  A common problem faced by teenage girls is dysmenorrhea, which requires serious attention from midwives. Appropriate health promotion, including media, must be attractive and accessible quickly and easily. The purpose of this study was to know the feasibility of a website-based educational media design for adolescent girls regarding the early treatment of dysmenorrhea. Methods: This research method uses the Research and Development (R&D) method.  The sample was 38 adolescent girls. Sampling used a purposive sampling technique calculated using the Slovin formula. The field test was conducted at SMK Negeri 1 Tasikmalaya City in April - May 2023. Data collection was carried out using interview methods and filling out questionnaires. The feasibility test was carried out by media experts and material experts. Results: The results of this Research and Development are website-based educational media "Sahabat Dysmenorrhea" which contains dysmenorrhea and early treatment of dysmenorrhea. In the validity test, an average percentage of 92% was obtained from material experts with a very feasible category and an average percentage of 88% from media experts with a very feasible category. The results of the small group trial were 94.24% with a very feasible category and the results of the field trial were 90.07% with a very feasible category. Conclusion: From the results of this study, it can be concluded that the “Sahabat Dysmenorrhea” website is very suitable for use as an educational media health promotion in dealing with dysmenorrhea in adolescent girls student.